EFISIENSI PERBANKAN SYARIAH DI INDONESIA: ANALISIS KOMPARATIF SEBELUM DAN SELAMA PANDEMI COVID-19 - Setiawan, Deri; Sandhi Prahara, Rahma (Jurnal Dinamika Ekonomi Syariah, 2025)
The Covid 19 pandemic is an outbreak of disease that was first discovered in the Chinese city of Wuhan and then spread throughout the world. The impact of the Covid 19 pandemic caused many fatalities and increased material losses. The existence of the Covid 19 pandemic caused significant losses to the Global economy, placing strong pressure on markets and financial institutions around the World. Thus this will cause differences in conditions before and during the Covid 19 pandemic. This study aims to determine the value of bank efficiency before and during the Covid 19 pandemic and to analyze the comparison of efficiency values between the two. This type of research is a quantitative method using Data Envelopment Analysis (DEA) Model Variable to Scale (VRS) and Mannwitney Test. The results of this study show that there is no significant difference between the conditions of Islamic Commercial Banks before and during the Covid 19 Pandemic. These results are in accordance with the results of the Mannwhitney Test which shows the value of Asymp.Sig(2-tailed) 776.